О классе нильпотентности мультипликативной группы модулярной групповой алгебры 2-группы диэдра - Коновалов, А.Б. (Український математичний журнал, 1995)
It is proved that the wreath product of a second-order group and the commutant of a dihedral group is imbedded into a multiplicative group of a modular group algebra of a dihedral group of order 2 n . This implies that the nilpotency class of the multiplicative group is equal to 2 n−2, i.e., to the order of the commutant of the dihedral group.